1988
DOI: 10.3109/15513818809022303
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Analysis of Placental Tissue in First Trimester Abortions

Abstract: The value of histologic evaluation in the analysis of material from first trimester abortions is not completely defined. We prospectively analyzed placenta and decidua from 75 first trimester, spontaneous abortions to ascertain if morphologic features were predictive of karyotype. The histologic features analyzed included hydropic villus change, villus fibrosis, villus scalloping with trophoblastic invaginations, atypical stromal cells, aggregates of lymphocytes in placenta or decidua, and acute inflammation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 5 publications
1
12
0
2
Order By: Relevance
“…This finding indicates that the effect of D&C on the endometrium should be investigated in each indication. Although the reason that the endometrium is thinner in patients with D&C performed for spontaneous abortion is not known, histologic changes, such as acute inflammation in the endometrium of a spontaneous abortion, 14 may be a factor. The present study was designed to observe endometrial thickness during a natural menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that the effect of D&C on the endometrium should be investigated in each indication. Although the reason that the endometrium is thinner in patients with D&C performed for spontaneous abortion is not known, histologic changes, such as acute inflammation in the endometrium of a spontaneous abortion, 14 may be a factor. The present study was designed to observe endometrial thickness during a natural menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have found it possible to correlate villous morphology with specific chromosomal abnormalities 7,8 or to differentiate between normal and abnormal karyotypes. 9 However, most have found no association between villous morphological features and chromosomal abnormalities, with the exception of partial molar triploidy. [10][11][12][13][14][15] One explanation for this apparent lack of success is that both euploid and aneuploid pregnancy failures are associated with villous morphological changes occurring after embryonic demise, related mainly to placental degeneration.…”
mentioning
confidence: 99%
“…As karyotyping was not done in our study, the association of abnormal karyotype with particular pattern of histopathological changes could not be ascertained. 17 In the present study, the mean age at the time of abortion was 25.09 ± 5.58 years with minimum age was 15 years and maximum age was 45 years. Majority of women belonged to age group 21-30 years (62.2%) while only 2.7% were above 40 years which shows highly significance.…”
Section: Discussionmentioning
confidence: 95%